LEVEL OF TOTAL TUMOR PROTEIN 53 IN THE SERA OFIRAQI BREAST CANCER PATIENTS - Hassan, Haider (Iraqi Journal of Science, 2024)
Breast cancer is one of the most common cancers in women. It occurs whenabnormal cells in the breast divide uncontrollably and form tumors. Mutation oftumor suppressor gene P53 is a common event in this disease.Level of total tumor protein 53 has been estimated in fifty serologic samples of Iraqibreast cancer patients and (50) of benign breast tumors as patients control inaddition to (50) serologic samples which belong to apparently health volunteers. Allthese patients were attending to the Teaching Hospital of Baghdad and Al-Elwiahospital during the period between October/2007 and (April) 2008. They werediagnosed as having breast cancer by clinical and laboratory investigation asultrasound waves test and fine needle aspiration (FNA). In addition to TP53, somehematological tests as hemoglobin, pocket cells volume, platelets count and whiteblood cells count were occurred. The current study revealed that (22%) out of totalmalignant breast cancer tumor patients were positive, while (8%) out of benignbreast tumors patients were positive for TP53. The mean value of TP53concentration in patients with breast cancer, benign tumors, and apparently healthygroups were (16.47 ± 31.81 pg/ml), (4.13 ± 4.94 pg/ml) and (2.27 ± 0.52pg/ml)respectively, with significant difference between malignant and benign cases.The evaluate TP53 test by application of Receiver Operator Characteristic (ROC)showed that the accuracy of TP53 was (57%), however its specificity was proposedto be (68%) in comparison with (53.33%) sensitivity.